The Implementation of Student Peer-Feedback in Writing Hortatory Exposition Text - Erlika Argianti Karsudin (Journal of English Education Program (JEEP), 2015)
This study reports on the implementation of student peer-feedback in writing hortatory exposition text, particularly at the eleventh grade in one of Senior High Schools in Banjar. Peer-Feedback is one of appropriate techniques to support students in learning writing. The writers adopted qualitative approach particularly a case study design as the research design. The writers conducted observation, interview to an English teacher and administered questionnaire for the students as well. In this case, the respondents were selected purposively. The results showed that the implementation of peer-feedback is useful to support and motivate the students to learn well. The students can be active in learning writing. In implementing peer-feedback, they can the students wrote, they analyzed their peer text. After that, they gave comments and revisions by giving circle and underline on their peer text, such as in the mechanics of writing, vocabulary and grammar error.Key words: writing, peer-feedback, hortatory exposition, perception